Implications of identifying the recently defined members of the Staphylococcus aureus complex S. argenteus and S. schweitzeri: a position paper of members of the ESCMID Study Group for Staphylococci and Staphylococcal Diseases (ESGS). (September 2019) - Becker, K.; Schaumburg, F.; Kearns, A.; Larsen, A.R.; Lindsay, J.A.; Skov, R.L.; Westh, H.
Abstract: Background: Staphylococcus argenteus and Staphylococcus schweitzeri, previously known as divergent Staphylococcus aureus clonal lineages, have been recently established as novel, difficult-to-delimit, coagulase-positive species within the S. aureus complex . Methicillin-resistant strains of S. argenteus are known from Australia and the UK. Knowledge of their epidemiology, medical significance and transmission risk is limited and partly contradictory, hampering definitive recommendations. There is mounting evidence that the pathogenicity of S. argenteus is similar to that of 'classical' S. aureus, while as yet no S. schweitzeri infections have been reported. Aim: To provide decision support on whether and how to distinguish and report both species. Sources: PubMed, searched for S. argenteus and S. schweitzeri . Content: This position paper reviews the main characteristics of both species and draws conclusions for microbiological diagnostics and surveillance as well as infection prevention and control measures. Implications: We propose not distinguishing within the S. aureus complex for routine reporting purposes until there is evidence that pathogenicity or clinical outcome differ markedly between the different species. Primarily for research purposes, suitably equipped laboratories are encouraged to differentiate between S. argenteus and S. schweitzeri . Caution is urged if these novel species are explicitly reported. In such cases, a specific comment should be added (i.e. 'member of the S.aureus complex') to prevent confusion with less- or non-pathogenic staphylococci. Prioritizing aspects of patient safety, methicillin-resistant isolates should be handled as recommended for methicillin-resistant Staphylococcus aureus (MRSA). In these cases, the clinician responsible should be directly contacted and informed by the diagnosing microbiological laboratory, as they would be for MRSA. Research is warranted to clarify the epidemiology, clinical impact and implications for infection control of such isolates .